"Souvenir Babies" and Abandoned Homes: Tracking the Reproductive Forces of Tourism - Frohlick, Susan (Anthropologica, 2015)
Reproduction occurs through processes of tourism and travel and across borders. This article explores the phenomenon of Euro-American women as mobile social actors bearing children out of relations with local men in Costa Rica and the various material-relational effects of their reproductive decisions. By looking at the pregnancies and bicultural children born out of transnational relations from various actors’ perspectives—foreign mothers, Costa Rican fathers and townspeople—contestations over the social and cultural meanings and motivations for cross-border reproduction become apparent. "Reproductive mobility" depends on how places are imagined and can lead to new opportunities for, as well as new inequities and rifts over, kinship formation.